Alignment between values of dryland pastoralists and conservation needs for small mammals. Issue 2 (14th December 2016) - Addison, Jane; Pavey, Chris R.
Abstract: Policies for conservation outside protected areas, such as those designed to address the decline in Australian mammals, will not result in net improvements unless they address barriers to proenvironmental behavior. We used a mixed‐methods approach to explore potential value‐action gaps (disconnects between values and subsequent action) for small mammal conservation behaviors among pastoralists in dryland Australia. Using semistructured surveys and open‐ended interviews (n = 43), we explored values toward small mammals; uptake of a range of current and intended actions that may provide benefit to small mammals; and potential perceived barriers to their uptake. Pastoralists assigned great conservation value to small mammals; over 80% (n = 36) agreed to strongly agreed that small mammals on their property were important. These values did not translate into stated willingness to engage in voluntary cessation of wild‐dog control (r 2 = 0.187, p = 0.142, n = 43). However, assigning great conservation value to small mammals was strongly related to stated voluntary willingness to engage in the proenvironmental behavior most likely to result in benefits to small mammals: cat and fox control (r 2 = 0.558, p = 0.000, n = 43). There was no significant difference between stated voluntarily and incentivized willingness to engage in cat and fox control (p = 0.862, n = 43). The high levels of willingness to engage in voluntary cat and fox control highlight a potential entry point for addressing Australia's mammal declines because the engagement of pastoralists in conservation programs targeting cat and fox control is unlikely to be prevented by attitudinal constraints. Qualitative data suggest there is likely a subpopulation of pastoralists who value small mammals but do not wish to engage in formal conservation programs due to relational barriers with potential implementers. A long‐term commitment to engagement with pastoralists by implementers will thus be necessary for conservation success. On‐property cat and fox control programs that build and leverage trust, shared goals, collaboration, and shared learning experiences between stakeholders and that explicitly recognize the complexity of small mammal dynamics and the property‐level ecological knowledge of pastoralists are more likely to gain traction.